2011
DOI: 10.1038/ejhg.2011.207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the somatic NF1 mutational spectrum associated with NF1 cutaneous neurofibromas

Abstract: Neurofibromatosis type-1 (NF1), caused by heterozygous inactivation of the NF1 tumour suppressor gene, is associated with the development of benign and malignant peripheral nerve sheath tumours (MPNSTs). Although numerous germline NF1 mutations have been identified, relatively few somatic NF1 mutations have been described in neurofibromas. Here we have screened 109 cutaneous neurofibromas, excised from 46 unrelated NF1 patients, for somatic NF1 mutations. NF1 mutation screening (involving loss-of-heterozygosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Although such misclassification of pathogenic variants as benign during training might lead to biased estimations, their overall frequency is expected to be low and therefore their relative impact on overall model performance is expected to be minor. Finally, we note that although gene-specific in-silico analysis such as the one described here may facilitate variant prioritization and functional assessment, functional characterization remains the gold standard for the definitive classification of variants [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although such misclassification of pathogenic variants as benign during training might lead to biased estimations, their overall frequency is expected to be low and therefore their relative impact on overall model performance is expected to be minor. Finally, we note that although gene-specific in-silico analysis such as the one described here may facilitate variant prioritization and functional assessment, functional characterization remains the gold standard for the definitive classification of variants [ 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, NF1 is considered a classic tumor suppressor gene and its mechanism in NF1 is felt to be consistent with Knudson's two-hit hypothesis in which a patient carries a mutated germline NF1 gene copy and tumor development, including CN, then requires a second hit[14]. While the germline mutations in NF1 are well cataloged, with >1000 mutations identified to date, there is a paucity of information on the assumed acquired somatic mutations in CN[15]. This deficiency is likely related to both the difficulty of detecting somatic mutations in CN due to cellular heterogeneity within the tumors and also the small number of CN analyzed.…”
Section: Discussionmentioning
confidence: 95%
“…However, the condition is very variable, even within families (for a review see [Pasmant et al, ]), and it is therefore thought that modifier genes, environmental effects and random events may also be important. Schwann cells in neurofibromas ([Bottillo et al, ; Thomas et al, ]) and melanocytes in café‐au‐lait patches [Maertens et al, ; De Schepper et al, ]) have been shown to have a mutation in both NF1 alleles, representing germline and acquired somatic mutations.…”
Section: To the Editormentioning
confidence: 99%